2008
DOI: 10.1242/dev.001081
|View full text |Cite
|
Sign up to set email alerts
|

Development of the renal glomerulus: good neighbors and good fences

Abstract: The glomerulus of the mammalian kidney is an intricate structure that contains an unusual filtration barrier that retains higher molecular weight proteins and blood cells in the circulation. Recent studies have changed our conception of the glomerulus from a relatively static structure to a dynamic one, whose integrity depends on signaling between the three major cell lineages: podocytes, endothelial and mesangial cells. Research into the signaling pathways that control glomerular development and then maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
184
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 146 publications
(138 reference statements)
5
184
0
1
Order By: Relevance
“…The zinc finger regions of WT-1 bind both DNA and RNA, and although WT-1 targets are unknown, mutations in WT-1 in humans lead to mesangial sclerosis and well-characterized glomerular lesions. 53,54 It has been suggested that WT-1 might regulate factors that affect vascular development, such as VEGF. 53 WT-1 may therefore influence the splicing of VEGF in podocytes and the associated glomerular phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The zinc finger regions of WT-1 bind both DNA and RNA, and although WT-1 targets are unknown, mutations in WT-1 in humans lead to mesangial sclerosis and well-characterized glomerular lesions. 53,54 It has been suggested that WT-1 might regulate factors that affect vascular development, such as VEGF. 53 WT-1 may therefore influence the splicing of VEGF in podocytes and the associated glomerular phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The major mechanisms that control vascular development in other systems have been the subject of excellent reviews [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and in the case of arteriolar development involve an active cross-talk between pericytes and ECs. Pericytes coat endothelial tubes, providing mechanical stability for the mature vessel, but they also partici- pate in the regulation of blood flow.…”
Section: Regulation Of Vascular Developmentmentioning
confidence: 99%
“…For other important regulatory molecules and mechanisms already demonstrated for nonrenal vessels, as well as for the development of the glomerular capillaries, the reader is referred to some excellent reviews. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In vivo, vascularization of the kidney is synchronized with epithelial nephrogenesis. Nephrogenesis of the definitive kidney results from the reciprocal inductive interaction between the primitive ureteric bud and the metanephric mesenchyme ( Figure 1).…”
mentioning
confidence: 99%
“…Nephrin is also a podocyte marker of mature glomeruli, and its timing of expression in podocytes during the capillary loop stage of nephrogenesis is implicated in the coordinated formation of foot processes and slit diaphragms as the podocyte adopts its articulated morphology and surrounds newly formed capillaries. 17,18 Although the general expression pattern of Rhophilin-1 and nephrin overlapped considerably, nephrin-positive, early capillary loop glomeruli forming toward the cortex did not express detectable amounts of Rhophilin-1 ( Figure 2B). On closer examination, Rhophilin-1 expression could be seen to lag spatiotemporally after nephrin expression was initiated in podocytes of the maturing glomerulus, because these cells predictably differentiate to enwrap the nascent capillary ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%